Molecular survey of arthropod-borne pathogens in sheep keds (Melophagus ovinus), Central Europe - Rudolf, Ivo; Betášová, Lenka; Bischof, Vlastimil; Venclíková, Kristýna; Blažejová, Hana; Mendel, Jan; Hubálek, Zdeněk; Kosoy, Michael (Parasitology research, 2016)
In the study, we screened a total of 399 adult sheep keds (Melophagus ovinus) for the presence of RNA and DNA specific for arboviral, bacterial, and protozoan vector-borne pathogens. All investigated keds were negative for flaviviruses, phleboviruses, bunyaviruses, Borrelia burgdorferi, Rickettsia spp., Anaplasma phagocytophilum, "Candidatus Neoehrlichia mikurensis," and Babesia spp. All ked pools were positive for Bartonella DNA. The sequencing of the amplified fragments of the gltA and 16S-23S rRNA demonstrated a 100 % homology with Bartonella melophagi previously isolated from a sheep ked and from human blood in the USA. The identification of B. melophagi in sheep keds in Central Europe highlights needs extending a list of hematophagous arthropods beyond ticks and mosquitoes for a search of emerging arthropod-borne pathogens.
Keywords: Arboviruses; Melophagus ovinus; Sequence Analysis, DNA; nemoci ovcí; Anaplasmataceae; ovce; Bartonella; Babesia; Česká republika; průzkumy a dotazníky; mužské pohlaví; Czech Republic; Sheep Diseases; Babesia spp.; Borrelia burgdorferi; Rickettsiae; Rickettsia; ženské pohlaví; zvířata; Anaplasma phagocytophilum; Surveys and Questionnaires; sekvenční analýza DNA; Sheep; Female; arboviry; Diptera; Bartonella melophagi; Male; Animals